2012
DOI: 10.1038/ncomms1638
|View full text |Cite
|
Sign up to set email alerts
|

Atom-specific spin mapping and buried topological states in a homologous series of topological insulators

Abstract: A topological insulator is a state of quantum matter that, while being an insulator in the bulk, hosts topologically protected electronic states at the surface. These states open the opportunity to realize a number of new applications in spintronics and quantum computing. To take advantage of their peculiar properties, topological insulators should be tuned in such a way that ideal and isolated Dirac cones are located within the topological transport regime without any scattering channels. Here we report ab-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
211
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(244 citation statements)
references
References 37 publications
22
211
2
3
Order By: Relevance
“…Some of these compounds possess extraordinary wide fundamental energy gaps and nearly ideal Dirac cones [8,15]. It was also shown that the modification of such features of the electronic structure as the position of the Dirac point relative to the Fermi level and to the bulk valence band edge, the absence of bulk conduction band states at the Fermi level, etc., can be efficiently controlled by means of a variation of the third component concentration [1,[5][6][7]9,20] or by diluted metal atom doping [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these compounds possess extraordinary wide fundamental energy gaps and nearly ideal Dirac cones [8,15]. It was also shown that the modification of such features of the electronic structure as the position of the Dirac point relative to the Fermi level and to the bulk valence band edge, the absence of bulk conduction band states at the Fermi level, etc., can be efficiently controlled by means of a variation of the third component concentration [1,[5][6][7]9,20] or by diluted metal atom doping [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that ternary compounds based on binary TIs show a rich variety of TSSs [3,8,9,[14][15][16][17] including buried TSSs [3,8] and occupied and unoccupied TSSs in local energy gaps [8,18,19]. Some of these compounds possess extraordinary wide fundamental energy gaps and nearly ideal Dirac cones [8,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that the electron dynamics of TSSs is dominated by the bulk conduction band, but did not provide scattering rates between TSS and the conduction or valence band. Such information could be related to results obtained from transport measurements and would be important for device applications.Complex ternary Sb 2 Te 3 -based alloys possess a layer structure with a van der Waals gap between Te layers and were recently proposed to exhibit a topological surface state [9][10][11]. However, intrinsic p doping of antimony-containing materials does not permit to access the Dirac point by conventional angle-resolved photoelectron spectroscopy [12] even after doping by alkali-metal atoms [13].…”
mentioning
confidence: 99%
“…Three-dimensional topological insulators (TIs), a novel class of materials in which an insulating bulk necessarily coexists with a metallic surface, have been attracting a great deal of attention for several years [1][2][3][4]. As a consequence of the strong spin-orbit coupling, the band gap in TIs gets inverted giving rise to a special type of surface states that have linear dispersion characteristic of Dirac fermions.…”
Section: Introductionmentioning
confidence: 99%